Three easy fixes for sire use can enhance genetic progress in community-based breeding programmes - Mueller, Joaquin Pablo; Getachew, Tesfaye; Rekik, Mourad; Rischowsky, Barbara; Abate, Zelalem; Goshme, Shenkute; Wale, Yeshiwas; Haile, Aynalem (Wiley, 2023)
We analysed options to optimize the use of sires in sheep and goat community-based breeding programmes (CBBP) for three scenarios occurring under field conditions: premature sale of selection candidates, fixed service periods of selected sires and incomplete sire pedigrees. The first scenario was studied by looking at the outcome of combinations of selection pressures in successive selection stages. A compromise of early sale of sire candidates and genetic progress can be obtained by selecting in two stages, such that selection pressure in the first stage is chosen in terms of achieving an acceptable selection potential after the second stage. Simulations showed the dependency of this compromise on selection accuracies and correlation between selection criteria. For a typical sheep CBBP, only 20% of the top three months weighting male lambs need to be retained to achieve 80% of the potential selection differential on six months weight. For the second scenario, two alternatives to fixed service periods were analysed. When across-age BLUP EBVs are not available, individual sires can be programmed to stay in service according to their initial ranking. In typical sheep, CBBPs genetic progress can be increased by about 9% over response to selection with optimum fixed sire service periods. When BLUP EBVs are available, a simulated retrospective analyses of across-age selection of sires in two current sheep CBBPs increased more than twofold the average breeding values actually observed. Thirdly, we studied the benefit of considering possible sires and their mating probabilities when estimating BLUP breeding values instead of setting such sires as unknown. In a current goat CBBP with up to three possible sires included in the pedigree, the accuracy of breeding values nears the accuracy when sires are known and are higher than accuracies when sires are unknown or when possible sires are ignored.